The life and legacy of Robert Ault, art therapy pioneer - Ault, Robert; Schmanke, Libby (New York, NY : Routledge, 2024)
"This accessible book provides an edited and annotated compilation of selections of Robert Ault's previously unpublished work, from presentations at psychiatric conferences to examples of his paintings and drawings. Ault's manuscripts for presentations, workshop protocols, and art therapy directives that are otherwise unavailable are of great value to current and future art therapists and clinicians in fields like expressive arts therapy, counseling, social work, and psychology. As a mentee and close friend of Ault's for the decade before his death, and with access to the full range of his unpublished and self-published material, author Libby Schmanke is ideally qualified to provide biographical and historical context and personal observations. This reference is beneficial for conceptualizing and applying art therapy, as well as having the historical value of preserving and honoring the work of a pioneer who sought to keep the art in art therapy"--
Keywords: Ault, Robert; Art therapy -- United States; ART / Individual Artist; PSYCHOLOGY / Psychotherapy / Counseling